Racial/ethnic differences in atrial fibrillation symptoms, treatment patterns, and outcomes: Insights from Outcomes Registry for Better Informed Treatment for Atrial Fibrillation Registry - Golwala, Harsh; Jackson, Larry R.; Simon, DaJuanicia N.; Piccini, Jonathan P.; Gersh, Bernard; Go, Alan S.; Hylek, Elaine M.; Kowey, Peter R.; Mahaffey, Kenneth W.; Thomas, Laine; Fonarow, Gregg C.; Peterson, Eric D.; et al. (The American heart journal, 2016)
Significant racial/ethnic differences exist in the incidence of atrial fibrillation (AF). However, less is known about racial/ethnic differences in quality of life (QoL), treatment, and outcomes associated with AF. Using data from the Outcomes Registry for Better Informed Treatment of Atrial Fibrillation, we compared clinical characteristics, QoL, management strategies, and long-term outcomes associated with AF among various racial/ethnic groups. We analyzed 9,542 participants with AF (mean age 74 ± 11 years, 43% women, 91% white, 5% black, 4% Hispanic) from 174 centers. Compared with AF patients identified as white race, patients identified as Hispanic ethnicity and those identified as black race were younger, were more often women, and had more cardiac and noncardiac comorbidities. Black patients were more symptomatic with worse QoL and were less likely to be treated with a rhythm control strategy than other racial/ethnic groups. There were no significant racial/ethnic differences in CHA2DS2-VASc stroke or ATRIA bleeding risk scores and rates of oral anticoagulation use were similar. However, racial and ethnic minority populations treated with warfarin spent a lower median time in therapeutic range of international normalized ratio (59% blacks vs 68% whites vs 62% Hispanics, P < .0001). There was no difference in long-term outcomes associated with AF between the 3 groups at a median follow-up of 2.1 years. Relative to white and Hispanic patients, black patients with AF had more symptoms, were less likely to receive rhythm control interventions, and had lower quality of warfarin management. Despite these differences, clinical events at 2 years were similar by race and ethnicity.